2020
DOI: 10.5433/1679-0359.2020v41n1p83
|View full text |Cite
|
Sign up to set email alerts
|

Sprouting, phenology, and maturation of the Italian grapevine ‘Fiano’ in Campo Largo, PR, Brazil

Abstract: Highlights:The Italian cultivar Fiano is productive and adapted to the region of Campo Largo. Sprouting of dormant buds can be increased with Erger in years of low chill. Wine production in the altitude region in the Paraná State may be a new economical option. AbstractDespite the expansion of viticulture in Brazil, the lack of chilling hours is a factor that requires the use of growth inducers to promote sprouting. Erger™ is a product of low toxicity and efficient in the bud induction of apple. However, there… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
3
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 19 publications
(19 reference statements)
4
3
2
Order By: Relevance
“…Our study showed statistical differences from 21 to 35 DADA (Table VI). These results agree with a previous report [10] that found a 95% sprouting in the Cumbe cultivar after applying HC at 1%, following manual defoliation, thus exposing the buds to the sprouting inducer. Without the application of this product, there is little sprouting, possibly due to apical dominance [19].…”
Section: B Sproutingsupporting
confidence: 93%
See 1 more Smart Citation
“…Our study showed statistical differences from 21 to 35 DADA (Table VI). These results agree with a previous report [10] that found a 95% sprouting in the Cumbe cultivar after applying HC at 1%, following manual defoliation, thus exposing the buds to the sprouting inducer. Without the application of this product, there is little sprouting, possibly due to apical dominance [19].…”
Section: B Sproutingsupporting
confidence: 93%
“…Various researchers [6]- [8] concluded that manual or chemical tree defoliation advances flowering and fruit harvest. In some cases, this could be improved with supplemental early pruning [9] or the use of sprouting inducers [10], [11] in an addressed way. In terms of defoliation, it is important to know when new flower buds are induced with subsequent flower formation, consequently, early defoliation causes the inhibition of immature buds.…”
Section: Introductionmentioning
confidence: 99%
“…In agreement with these results, it has been observed in grapevine that, under subtropical conditions, plants sprayed with an Erger R solution, and plants treated with hydrogen cyanamide (3.5-4.5%) solutions present similar vegetative bud break rates (Fowler et al, 2020). Even so, both Erger R and hydrogen cyanamide treatments exhibited a higher budburst (10-15%) than the control treatment (Fowler et al, 2020;Rosa et al, 2020).…”
Section: Alternatives To Hydrogen Cyanamide Based On Nitrogen Compoundssupporting
confidence: 72%
“…Erger ® + Activ Erger ® have been widely applied in many different species like apple, grapevine, kiwi [ Actinidia deliciosa (A.Chev.) C.F.Liang & A.R.Ferguson], blackberry, sweet cherry and peach to promote endodormancy release, and flowering ( Segantini et al, 2015 ; Ardiles and Ayala, 2017 ; Pasa et al, 2018 ; Ferreira et al, 2019 ; Fowler et al, 2020 ).…”
Section: Effects Of Agrochemicals On Endodormancy Releasementioning
confidence: 99%
“…The proposed molecular mechanisms of HC have assisted in developing less toxic commercial alternatives, such as plant biostimulants (PBs), which have been sold amongst agrochemical products over the last few years. Indeed, several PBs have shown a potential to enhance bud-break, compared to no treatment, in apple, grapevine, pear, sweet cherry, blackberry, peach, and kiwi [29][30][31][32][33][34][35][36]. However, very few reports, especially in the grapevine, exist of PBs that enhanced bud-break in a similar or superior manner to that of HC.…”
Section: Introductionmentioning
confidence: 99%